Are Elevated Nicotine and Cotinine Levels Associated with Early Femoral Component Subsidence in Press-Fit, Primary Total Hip Arthroplasty? - Muffly, Brian T.; Jacobs, Cale A.; Duncan, Stephen T. (The Journal of Hip Surgery, 2020)
Tobacco exposure negatively affects bone mineral density and early osseointegration of surgical implants. We sought to determine if elevated nicotine and/or cotinine levels prior to primary total hip arthroplasty (THA) are associated with early femoral component subsidence. We hypothesize that tobacco users will have higher rates of readmission/reoperation and increased radiographic subsidence. We conducted an institutional review of 75 patients (average age = 52.9 years; 55% females; body mass index = 31.3) who underwent THA from April 2017 to January 2018. Immediate postoperative radiographs were compared with those obtained at 2 to 6 weeks postoperatively to determine early femoral component subsidence. Of the 75 patients, 10 (13.3%) had early radiographic femoral component subsidence ≥ 2 mm. In this group, preoperative nicotine levels were significantly elevated (7.2 vs. 1.5ng/mL; p = 0.04), whereas preoperative cotinine levels did not statistically differ (108.3 vs. 33.8 ng/mL; p = 0.45). A significantly greater magnitude of subsidence was seen in those with elevated preoperative nicotine levels compared with those with normal levels (1.7 vs. 0.5 mm; p = 0.04). The mean time to radiographic follow-up was 2.6 weeks. Surgical approach, implant type, categorical variables, and patient readmission were not associated with ≥ 2 mm of early subsidence. There was a single reoperation for periprosthetic fracture, but none was related to instability from subsidence. Early femoral component subsidence was more prevalent in patients with elevated preoperative nicotine levels. Rates of readmission/reoperation at 90 days did not differ between those with and without elevated tobacco markers. Clinically relevant thresholds of preoperative nicotine and/or cotinine values are needed to better delineate appropriate surgical candidates to achieve optimal surgical outcomes.
Keywords: early femoral component subsidence; tobacco; primary total hip arthroplasty; nicotine; cotinine